Need of Online Workshops for Research Methodology: Perception study of Indian Ph.D. Research Scholars - Singh, Paramveer (Journal of Advanced Research in Journalism & Mass Communication, 2017)
Main Objective of this study is to know the perception of Indian Research Scholars toward need of online workshops for research methodology. Total 25 research scholars surveyed for this study through online survey. Questionnaire was formed in Google form and sent to the research Scholar through Email. 5 research scholars from each region of the country (east, west, north, south and central) were took as sample for this study. Study reveals that most of the scholars think that online workshop can be better than traditional workshops for research methodology. Research Scholars thinks that they feel difficulty to find content online related to their research. They suggest that research scholars must empower with internet facility to do quality research. How to cite this article: Singh P. Need of Online Workshops for Research Methodology: Perception study of Indian Ph.D. Research Scholars. J Adv Res Jour Mass Comm 2017; 4(3&4): 73-81. DOI: https://doi.org/10.24321/2395.3810.201702